1991
DOI: 10.1002/jnr.490280110
|View full text |Cite
|
Sign up to set email alerts
|

Serial passage of embryonic human astrocytes in serum‐free, hormone‐supplemented medium

Abstract: We applied serum-free cell culture methods that allow extended proliferation of mouse astrocyte precursor cells to the multipassage culture of embryonic human brain cells. Cells were cultured in nutrient medium supplemented with insulin, transferrin, epidermal growth factor, fibroblast growth factor, heparin, high-density lipoprotein, and fibronectin. Cultures were maintained for a maximum of 70 population doublings before proliferation ceased. The cells synthesized glial fibrillary acidic protein, an astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…HDLs and growth factors have been reported to support the long-term growth of several cell types in serum-free conditions while maintaining their morphological and biological characteristics (Gospodarowicz, 1984;Loo et al, 1989Loo et al, , 1991Sakai et al, 1990). In the present work, using a basal medium containing HDLs, FGF-2, insulin, and transfen'in, we demonstrated that serum could be omitted in CCL39, bSM, and EA.hy926 cell cultures.…”
Section: Discussionsupporting
confidence: 53%
“…HDLs and growth factors have been reported to support the long-term growth of several cell types in serum-free conditions while maintaining their morphological and biological characteristics (Gospodarowicz, 1984;Loo et al, 1989Loo et al, , 1991Sakai et al, 1990). In the present work, using a basal medium containing HDLs, FGF-2, insulin, and transfen'in, we demonstrated that serum could be omitted in CCL39, bSM, and EA.hy926 cell cultures.…”
Section: Discussionsupporting
confidence: 53%
“…Especially the long-term maintenance of the cells in EGF, which has to be added immediately to the primary cultures, appears to be a mandatory experiment according to our own experiment and the experience of others (Loo et al, 1987). In contrast to experiments with rodent embryonal brain cells (Loo et al, 1991), however, maintenance in serum free conditions alone failed to sustain proliferation or expand in vitro passages. Clinically it is known that neurocytomas are best treated by removal and subsequent irradiation; they are not known to produce other than local recurrencies (Nishio et al, 1988;Yasargil et al, 1992;Kim et al, 1992).…”
Section: Discussionmentioning
confidence: 85%
“…Especially the long-term maintenance of the cells in EGF, which has to be added immediately to the primary cultures, appears to be a mandatory experiment according to our own experiment and the experience of others (Loo et al, 1987). In contrast to experiments with rodent embryonal brain cells (Loo et al, 1991), however, maintenance in serum free conditions alone failed to sustain proliferation or expand in vitro passages.…”
Section: Discussionmentioning
confidence: 87%
“…A4, the principal component of these deposits, corresponds to an APP sequence extending from the middle of the transmembrane domain to the proximal extracellular region. APP is normally cleaved in some neural and nonneural cells within the extracellular portion of A4 (Anderson et Rapidly dividing (passage 20) and slowly dividing (passage 55) human HBIB astrocytes were maintained in serum-free media supplemented with EGF and FGF as previously described (Loo et al, 1991). Neuroblastomas N-GP, N-LF, N-MB (obtained from Dr. G. Brodeur), IMR-32, and SK-SH-5Y and control or F-AD fibroblasts (AG04402A) obtained from the ATTC were maintained in Waymouth's MB media with 10% fetal calf serum.…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly dividing (passage 20) and slowly dividing (passage 55) human HBIB astrocytes were maintained in serum-free media supplemented with EGF and FGF as previously described (Loo et al, 1991). Neuroblastomas N-GP, N-LF, N-MB (obtained from Dr. G. Brodeur), IMR-32, and SK-SH-5Y and control or F-AD fibroblasts (AG04402A) obtained from the ATTC were maintained in Waymouth's MB media with 10% fetal calf serum.…”
Section: Introductionmentioning
confidence: 99%